2016
DOI: 10.1109/te.2015.2417512
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Network Security With IP Darkspace Data

Abstract: This paper presents a network security laboratory project for teaching network traffic anomaly detection methods to electrical engineering students. The project design follows a research-oriented teaching principle, enabling students to make their own discoveries in real network traffic, using data captured from a large IP darkspace monitor operated at the University of California, San Diego (UCSD). Although darkspace traffic does not include bidirectional conversations (only attempts to initiate them), it con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The authors suggested a group-based strategy in which students have access to workstations that have the CommView network analysis and packet sniffing programs installed. A similar proposal, geared towards security auditing practice activities is proposed in [8], which presents a methodology for teaching network traffic anomaly detection techniques utilizing an IP darkspace monitor, resorting to the MATLAB, tcpdump, corsaro, and RapidMiner tools. They also present a concept for a network security laboratory, designed for instructional purposes.…”
Section: A Quick Review Of Testbeds and Cyber Ranges For Training And Researchmentioning
confidence: 99%
“…The authors suggested a group-based strategy in which students have access to workstations that have the CommView network analysis and packet sniffing programs installed. A similar proposal, geared towards security auditing practice activities is proposed in [8], which presents a methodology for teaching network traffic anomaly detection techniques utilizing an IP darkspace monitor, resorting to the MATLAB, tcpdump, corsaro, and RapidMiner tools. They also present a concept for a network security laboratory, designed for instructional purposes.…”
Section: A Quick Review Of Testbeds and Cyber Ranges For Training And Researchmentioning
confidence: 99%
“…Instructor scored the accepted experimental works; the score was taken as the instantiation of Mark which ranged in [0,2]. The total score of each student taking part in crowdsourcing must range in [3], [5]. If the score exceeds 5, a certain amount of money would be paid to the student, which was the instantiation of Money.…”
Section: ) Fim Instantiation and Analysismentioning
confidence: 99%
“…these experiments from realistic scenarios that are shown to be more popular with the faculties and students [3].…”
Section: Introductionmentioning
confidence: 99%
“…For understanding security auditing methods, Zseby et al 5 proposed a project for teaching network traffic anomaly detection methods using a large IP darkspace monitor operated at the University of California, San Diego (UCSD). The exercises are based on four software tools, including, tcpdump, corsaro, MATLAB, and RapidMiner.…”
Section: Related Workmentioning
confidence: 99%